1648. CD4 T Lymphocyte and Monocyte Activation within One Year After Treatment Completion for Pulmonary Tuberculosis: A Pilot Study. (31st December 2020) - Huaman, Moises A; Moussa, Anissa; Orsborn, Kris I; Ticona, Eduardo; Sanchez, Jorge; Zavaleta, Milagros; Sterling, Timothy; Chougnet, Claire; Deepe, George S; Fichtenbaum, Carl
Abstract: Background: Persons with active tuberculosis (TB) have increased immune activation, which declines with TB treatment. Whether residual immune activation is present after completion of TB treatment is unknown. We conducted immunophenotyping of T cells and monocytes from individuals who had completed TB treatment, and compared them to controls without history of active TB. Methods: Cross-sectional study of HIV-uninfected individuals 40 to 70 years old recruited in Lima, Peru. For this analysis, we included 6 individuals who had completed treatment for pulmonary TB within the past year, and 10 healthy controls without history of active TB (6 QuantiFERON®-TB positive; 4 QuantiFERON®-TB negative). Participants provided blood for T cell and monocyte immunophenotyping using multi-parameter flow cytometry, including expression of cell surface activation markers. Results: There were no significant differences in age, sex, or comorbidities between patients previously treated for TB and controls without history of active TB. Median time since TB treatment completion was 4 months (range, 2 – 9) for the previously treated group. Compared to controls, persons previously treated for TB had increased CD4 + to CD8 + ratio (2.4 vs. 1.3; p =0.03), increased proportion of CD4 + T cells co-expressing HLA-DR and CD38 activation markers (5.8% vs. 3.1%; p =0.02), increased CD4 + T cell ICAM-1 expression (56.3% vs. 33.2%; p =0.03), as well as increased density of HLA-DR in monocytes (HLA-DR MFI; 7572 vs. 3917; p =0.03). Conclusion: In this pilot study, individuals who recovered from pulmonary TB exhibited increased CD4 + T cell and monocyte activation phenotypes within one year of TB treatment completion. These results suggest residual immune activation after clinical TB cure. Disclosures: Carl Fichtenbaum, MD, Amgen (Grant/Research Support, outside the submitted work)Clinical Care Options (Other Financial or Material Support, outside the submitted work)Cytodyn (Grant/Research Support, outside the submitted work)Gilead Sciences (Grant/Research Support, outside the submitted work)Janssen (Grant/Research Support, outside the submitted work)Merck (Grant/Research Support, outside the submitted work)ViiV Healthcare (Research Grant or Support, outside the submitted work)